The effects of airline alliances: what do the aggregate data say? - Philippe Gagnepain; Pedro L. Marín (SERIEs - Journal of the Spanish Economic Association, 2010)
We consider an empirical model of worldwide airline alliances that we apply to a large set of companies for the period 19952000. Using observations at the network level, we estimate a cost, capacity, and demand system that accounts for cross-price elasticities. Our contribution consists in evaluating airlines' strategical interactions through the window of firms' network interconnections.We consider networks coincidences and potential connections with all their rivals. The results allow us to classify all company pairs as either complements or substitutes. We shed light on the fact that many airlines involved in the same alliance are potential substitutes.
Keywords: L11; L13; L41; 330; alliance; airline; cross-price elasticities; Strategische Allianz; Luftverkehrsgesellschaft; Preiselastizität; Unvollkommener Markt; Welt